THE EFFECT OF ABNORMALITIES OF ARTICULATORY ORGANS ON SPEECH FUNCTION - Manzurakhon Adilova (Journals Park Publishing, 2024)
This research article aims to review and analyse existing research in this area, identifying major trends and gaps in knowledge, and supports the importance of further research to optimise the diagnosis and correction of maxillofacial and myofunctional disorders in the context of ensuring the full development of speech in children.
Keywords: speech therapy, myofunctional disorders, articulation apparatus, correction, anomaly, deformation, parafunction, myotherapy.